Excel VBA programming for dummies - Walkenbach, John (Wiley, 2013)
Take control of your spreadsheets and use VBA to create your own custom Excel applications Author and Excel guru John Walkenbach, known to his devoted fans as "Mr. Spreadsheet," guides you through taking your Excel skills to the next level by creating your own customized spreadsheet solutions using Visual Basic for Applications (VBA). This updated edition of this bestselling book shows you how to use VBA, write macros, customize your Excel apps to look and work the way you want, avoid errors, and more. Introduces you to a wide array of new Excel 2013 options, beginning with the most important tools and operations for the Visual Basic Editor Provides an overview of the essential elements and concepts for programming with Excel, including using VBA to customize your applications and automate functions Shares techniques for handling errors, debugging, working with range objects, controlling flow, and much more Zeroes in on creating custom dialog boxes, toolbars, and menus Add a personal touch to your spreadsheets and present your data the way you want with Excel VBA Programming For Dummies, 3rd Edition.